Early-modern globalization and the extent of indigenous agency: Trade, commodities, and ecology - Ann M. Carlos; Erik Green; Calumet Links; Angela Redish (Queen's University Centre for Economic History (QUCEH), 2024)
This paper examines the responses of Indigenous nations and European companies to new trading opportunities: Cree nations and the Hudson's Bay Company (HBC), and Khoe nations and the Dutch East India Company (VOC). This case study is important because of the disparate outcomes: within a few decades the Cree standard of living had increased, and Khoe had lost land and cattle. Standard histories begin with the establishment of trading posts but this elides the decades of prior intermittent contact which played an important role in the disparate outcomes in the two regions. The paper emphasizes the significance of Indigenous agency in trade.
Keywords: N30; N70; N71; N77; J15; Q57; 330; Indigenous economics; trade; ecology; cross-continental comparison